Fatigue Assessment of Ti–6Al–4V Circular Notched Specimens Produced by Selective Laser Melting - Razavi, S.M.J.; Ferro, P.; Berto, F. (Проблемы прочности, 2017)
This work is aimed to assess the fatigue strength of Ti–6Al–4V smooth and circular notched samples produced by selective laser melting (SLM). Scanning electron microscopy have been used to investigate the fracture surface of the broken samples in order to identify crack initiation points and fracture mechanisms. Despite the observed fatigue strength reduction induced by circular notch compared to that of sooth specimens, notched samples showed a very low notch sensitivity attributed both to hexagonal crystal lattice characteristics of tempered alpha prime grains and to surface defects induced by the SLM process itself.